2013
DOI: 10.1002/jbio.201300135
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide evanescent field scattering microscopy: bacterial biofilms and their sterilization response via UV irradiation

Abstract: Waveguide Evanescent Field Scattering (WEFS) microscopy is introduced as a new and simple tool for label-free, high contrast imaging of bacteria and bacteria sensors. Bacterial microcolonies and single bacteria were discriminated both by their bright field images and by their evanescent scattering intensity. By comparing bright field images with WEFS images, the proportion of planktonic: sessile (i.e., "floating": attached) bacteria were measured. Bacteria were irradiated with UV light, which limited their bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Fluorescence imaging executed by surface-confined illumination, predominantly TIRF microscopy, has been extensively used to study subcellular processes occurring at, or in close proximity to, the cell membrane–substrate interface, including, for example, substrate-induced stimuli that induce changes in cell morphology, cell motility, and formation of focal adhesions. ,, Waveguides have been used for this purpose and, although predominantly in combination with fluorescence labeling, ,, direct utilization of evanescent-field induced scattering signals for detection of bacterial biofilm growth has also been reported . We were curious to investigate if the low stray light background offered by our waveguide design could allow label-free imaging of cellular attachment in a fashion similar to what is achievable with reflection interference contrast (RIC) microscopy, which enables cellular adhesion to be visualized with subcellular resolution by probing spatial variations near the cell–substrate interface .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence imaging executed by surface-confined illumination, predominantly TIRF microscopy, has been extensively used to study subcellular processes occurring at, or in close proximity to, the cell membrane–substrate interface, including, for example, substrate-induced stimuli that induce changes in cell morphology, cell motility, and formation of focal adhesions. ,, Waveguides have been used for this purpose and, although predominantly in combination with fluorescence labeling, ,, direct utilization of evanescent-field induced scattering signals for detection of bacterial biofilm growth has also been reported . We were curious to investigate if the low stray light background offered by our waveguide design could allow label-free imaging of cellular attachment in a fashion similar to what is achievable with reflection interference contrast (RIC) microscopy, which enables cellular adhesion to be visualized with subcellular resolution by probing spatial variations near the cell–substrate interface .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, no special requirements are placed on the objective used for signal collection, as is the case for in-lens TIR, where specially designed high magnification and high numerical aperture objectives with built-in optical path control must be employed. Most of the above-mentioned benefits of waveguide-based microscopy have already been demonstrated for fluorescently labeled probes, while advantages offered by label-free detection through evanescent-light-induced scattering of nanoscopic particles has only been moderately explored, and so far with emphasis on synthetic grid film-like structures, gold nanoparticles, , virions and bacterial biofilms, including attempts to study the forces acting on a particle through the evanescent field . Herein, we introduce a simple waveguide-based technique for simultaneous fluorescent and high sensitivity scattering imaging of surface immobilized objects to investigate interfacial biological processes not studied in this label-free way before.…”
mentioning
confidence: 99%
“…Waveguide evanescent field scattering microscopy was introduced as a new and simple tool for label‐free, high contrast imaging of bacteria and bacteria sensors. Bacterial microcolonies and single bacteria were discriminated both by their bright field images and by their evanescent scattering intensity .…”
Section: Biosensors For Biomarker Detectionmentioning
confidence: 99%
“…In addition, Nahar et al have shown that the UV illumination dose of 30 mJ/cm 2 was not sufficient to completely stop the attachment of Nitrobacter spp. 263 to the surface [8]. Also, L. pneumophila as well as a large number of other human pathogens are described to be able to enter the viable but nonculturable (VBNC) state [9] allowing bacteria to resist natural stress, such as starvation, temperatures outside the range of bacterial growth, high concentration of oxygen [10], or chlorination of water [9].…”
Section: Introductionmentioning
confidence: 99%